2020
DOI: 10.1155/2020/8822999
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady MHD Bionanofluid Flow in a Porous Medium with Thermal Radiation near a Stretching/Shrinking Sheet

Abstract: This research aims at providing the theoretical effects of the unsteady MHD stagnation point flow of heat and mass transfer across a stretching and shrinking surface in a porous medium including internal heat generation/absorption, thermal radiation, and chemical reaction. The fundamental principles of the similarity transformations are applied to the governing partial differential equations (PDEs) that lead to ordinary differential equations (ODEs). The transformed ODEs are numerically solved by the shooting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Irfan et al [8] examined the theoretical impact of magnetized stagnation point flow on heat and mass transfer towards a shrinking and stretching porous surface. Furthermore, they elaborated the behavior of chemical reaction, thermal radiation, swimming of gyrotactic microorganisms, and heat source/sink.…”
Section: Recent Advances In Multiphase Flows In Engineeringmentioning
confidence: 99%
“…Irfan et al [8] examined the theoretical impact of magnetized stagnation point flow on heat and mass transfer towards a shrinking and stretching porous surface. Furthermore, they elaborated the behavior of chemical reaction, thermal radiation, swimming of gyrotactic microorganisms, and heat source/sink.…”
Section: Recent Advances In Multiphase Flows In Engineeringmentioning
confidence: 99%
“…Working in the domain of nonlinear fluid flows creates challenges to the mathematician and simulation engineers with its diversity and complexity. As the complexity of such fluids offers no unique constitutive equation which encounters all the properties, for such fluids, several non-Newtonian models are presented in [1][2][3][4]. e polymeric liquids reveal diverse rheological attributes apparent in the flow, such as polymer accumulation, mechanical mortification, and solvent composition.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that on enhancing the viscosity and magnetic parameter, heat flux diminishes. Irfan et al 41 reported the influence of chemical reaction and internal heat generation/absorption on a radiative bio-nanofluid flow past a deforming surface with stagnation point flow in a porous chamber. On a time-dependent viscous fluid flow, Rosali et al 42 investigated transmission of heat amalgamated with stagnation point flow past a deforming surface with porosity effect.…”
Section: Introductionmentioning
confidence: 99%